Audit Sistem Informasi Pembelian Barang Pt Bumi Indah Saranamedis Menggunakan Framework Cobit 5 Domain Mea - Winanti, Linda Anjar; Nurmalasari, Nurmalasari (Journal of Information System, Applied, Management, Accounting and Research; Vol 9 No 1 (2025): JISAMAR (December-February 2025), 2025)
In the purchase process at PT. Bumi Indah Saranamedis involves several divisions ranging from the front office, and purchasing department to the warehouse. The purchase information system made by purchase orders relies on sales orders and stock cards. The issuance of purchase orders in the form of hard copies, methods of filling incoming goods files which include Purchase Orders, Good Receive Notes, and road letters or incoming goods invoices. Internal control system of the computer system by the relevant officer and manual by the warehouse officer. The purchasing process has several obstacles from the server system that is easily down or from human resources there is a human error, this greatly hampers the purchase work because it has to wait for IT to track and fix which parts there are errors. Evaluation of the company's performance and operations from the information system used and the people involved must be audited using the COBIT 5 standard. The COBIT 5 framework is very appropriate to be used to measure the level of maturity in the process of purchasing goods using the MEA (Monitoring, Evaluation, and Assess) domain. The results of research that has been conducted on the purchase information system at PT. Bumi Indah Saranamedis is already at level 4, namely Predictable, the process already has consistent limits. The system of purchasing goods is approaching the maximum level of maturity, it's just that there are still obstacles in some parts. The purchase process in this company is at an index of 4.3 with a Maturity Level 4 level. The results obtained can be used as a reference to create or add new rules to achieve effective performance and minimize the occurrence of errors, both from the system and human resources.